The Architecture of Facework in Intercultural Virtual Work Team - Setijadi, Naniek Novijanti (JURNAL KOMUNIKASI INDONESIA, 2019)
The most crucial aspect of a collaborative process, face to face or online, is the face of participants, which is the focus of this research. The face is a direct indicator of the importance for individuals to maintain face (self-esteem) for themselves and for their culture group. This research uses a qualitative interpretive approach of ethnomethodology. The subjects observed in this study are a virtual team of three universities: (one from Indonesia and two from the USA), which meets regularly via Skype videoconferencing. Conversation analysis is used to analyze how participants construct their conversation in collaborating to make decisions. The result of this study is the construction or mapping of the individual facework strategies from individualistic and collectivistic cultures. The implication of this research is a model constructing face strategy mapping of individuals, which explains how individuals negotiate their face in virtual collaboration inter-culturally and are very relevant in the advancement of Face-Negotiation Theory.